Realistic Mathematics Education Approach with the Assistance of Augmented Reality Media to Improve Elementary School Students' Mathematics Learning Outcomes - Lubis, Azmil Hasan; Idris, Aisyah (MANDAILING GLOBAL EDUKASIA, 2025)
Mathematics is a subject that every student must master. However, mathematics remains a traumatic experience for most students. This impacts students' low mathematics learning outcomes. This study aims to improve elementary school students' mathematics learning outcomes using a realistic mathematics education approach assisted by augmented reality media. This study is a classroom action research consisting of three cycles. Each cycle goes through four stages of activity: planning, action, observation, and reflection. The subjects of this study were fourth-grade students of SD Negeri 69 Banda Aceh. Data for this study were collected using observation and test techniques. Observations were used to measure teacher and student learning activities, while tests were used to measure improvements in students' mathematics learning outcomes. The results of the study indicate that the realistic mathematics education approach assisted by augmented reality media can improve elementary school students' mathematics learning outcomes. This can be seen in the average scores on the test results which show an increase in each cycle, namely 44.57 (pre-cycle), 63.07 (first cycle), 75.66 (second cycle), and 87.35 (third cycle). Based on this, the realistic mathematics education approach assisted by augmented reality media can be used as an alternative to solve the problem of low mathematics learning outcomes of students in elementary schools.